2021
DOI: 10.3389/fphar.2021.747450
|View full text |Cite
|
Sign up to set email alerts
|

Eicosanoid Metabolomic Profile of Remdesivir Treatment in Rat Plasma by High-Performance Liquid Chromatography Mass Spectrometry

Abstract: Remdesivir, a nucleotide analog prodrug, has displayed pharmacological activity against SARS-CoV-2. Recently, eicosanoids are widely involved in regulating immunity and inflammation for COVID-19 patients. Rats were intravenously administered remdesivir at a dose of 5 mg/kg, and series of blood samples were collected before and after treatment. Targeted metabolomics regarding the eicosanoid profile were investigated and quantitated simultaneously using the previously reported reliable HPLC-MS/MS method. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Both PCA and OPLS-DA were used to integrate and co-analyze all data to explore the longitudinal metabolic trajectory in all rats. Individuals were utilized as the grouping basis, and dots of the same color represented samples of one rat at different time points ( Du et al, 2021a ). From the results of Figure 2A , plasma samples of one rat were divided into tight clusters, which indicated that the longitudinal metabolic fingerprint of the same rat was relatively stable after remdesivir treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PCA and OPLS-DA were used to integrate and co-analyze all data to explore the longitudinal metabolic trajectory in all rats. Individuals were utilized as the grouping basis, and dots of the same color represented samples of one rat at different time points ( Du et al, 2021a ). From the results of Figure 2A , plasma samples of one rat were divided into tight clusters, which indicated that the longitudinal metabolic fingerprint of the same rat was relatively stable after remdesivir treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Limited studies have been revealed for the metabolite changes among COVID-19 patient cohorts, such as cytosine and tryptophan–nicotinamide pathways ( Blasco et al, 2020 ), lipids ( Archambault et al, 2021 ), amino acids and fatty acids ( Shen et al, 2020 ), and eicosanoids ( Du et al, 2021a ). However, to the best of our knowledge, no comprehensive metabolic profiling literature studies were reported pertaining to remdesivir treatment both in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when Bjork and Wallace [23] assessed the dose-dependent effect of remdesivir on mitochondrial DNA replication by exposing human hepatoma HepG2/C3A cells to increasing concentrations of remdesivir (0.1 to 10 µM) for 24 h and 48 h, they did not observe changes in mtDNA copy number. Given the pharmacokinetics of remdesivir in rats [33], our daily dose of 4.25 mg/kg of remdesivir is comparable to the human dose of 1.25mg/kg. The effects of remdesivir on the accumulation of mtDNA deletion mutations has received very little attention.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, when Bjork and Wallace [ 26 ] assessed the dose-dependent effect of remdesivir on mitochondrial DNA replication by exposing human hepatoma HepG2/C3A cells to increasing concentrations of remdesivir (0.1 to 10 μM) for 24 h and 48 h, they did not observe changes in mtDNA copy number. Given the pharmacokinetics of remdesivir in rats [ 38 ], our daily dose of 4.25 mg/kg of remdesivir is comparable to the human dose of 1.25 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…concentrations of remdesivir (0.1 to 10 μM) for 24 h and 48 h, they did not observe changes in mtDNA copy number. Given the pharmacokinetics of remdesivir in rats [38], our daily dose of 4.25 mg/kg of remdesivir is comparable to the human dose of 1.25 mg/kg.…”
Section: Plos Onementioning
confidence: 97%